La ecología alimentaria del pez endémico Girardinichthys multiradiatus(Cyprinidontiformes: Goodeidae), en el Parque Nacional Lagunas de Zempoala, México - Trujillo Jiménez, Patricia (2006)
Girardinichthys multiradiatus, locally known as “mexcalpique”, is a small endemic fish of the Lerma river basin. Its presence in lakes (Zempoala) suggests a long-standing connection between these lakes and the river basin. The current range of this species in the Mexico and Toluca valley appears to have been reduced, making this park a refuge for the species. Nevertheless, little is known about its biology. We studied its diet and feeding habits in Acoyotongo Lake, Lagunas de Zempoala National Park (19°01’30”-19°06’ N, 99°16’20”-99°21’ W) where seasonal collections were carried out. The gut contents of 97 specimens were identified to the most specific taxonomic category possible and analyzed with numeric and frequency of occurrence methods. The general diet of this species consists of twelve dietary components, eleven of which are of animal origin. Hymenopterans, springtails and chironomids represented the highest percentage of ingestion and preference. G.multiradiatus is as a carnivorous species with entomophagous tendencies.